Pengaruh Pertumbuhan Ekonomi Terhadap Ketimpangan Pendapatan di Kota Medan Tahun 2016–2024 - Rizki Afifah Hasibuan; Irsad Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the influence of economic growth on income inequality in Medan City during the period 2016–2024. Using annual data obtained from the Central Bureau of Statistics (BPS), the research employs a quantitative approach through regression analysis using EViews to identify whether economic growth contributes to reducing or increasing inequality. The results indicate that economic growth significantly affects the Gini Index, although the direction of influence fluctuates across years due to structural changes in the urban economy, labor market disparities, and uneven distribution of development benefits. This study emphasizes the importance of inclusive economic policies to ensure that growth outcomes are evenly shared across all socioeconomic groups.